Freedom in the work of F.A Hayek and John Rawls - De Freitas Faisst, Alexandre (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
This article compares the concept of freedom in the works of Friedrich Hayek and John Rawls. Its purpose is to comparatively analyze such concepts with a view of the political-legal scope and their conceptions of liberalism. Based on similar elements, Hayek’s idea of freedom is analyzed according to the works Road to Serfdom (1945) and Constitution of Liberty (1960), and Rawls’ from the books A Theory of Justice (1971) and Political Liberalism (1993). Although both are within the broad tradition of liberalism, they diverge on many points, bringing Rawls closer to deliberative democracy and Hayek to libertarianism.